The Development of Community Learning Center (CLC) Management Model to Improve Non-Formal Education Service Quality - Asep Saepudin; Ade Sadikin; Iip Saripah (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2021)
This research focused on analyzing the implementation of a service model used in a community learning center (CLC). The results of the study are (1) a conceptual model consisting of rationalization, assumptions, goals, components, indicators, and procedures, (2) a model validated through peer group discussion and expert judgment, and (3) a model implemented in universities. The learning model developed consists of planning, organizing, implementing, and assessing processes. Based on the results, it is concluded that the developed model shows an effective result based on some indicators. The first indicator is the community active involvement and positive responses to the learning process. Then, there is an improvement in terms of knowledge, attitudes, and skills of the community